INCREASING THE USEFUL SURFACE OF THE MESH SURFACE - Sultanov, Sahobiddin; Salomova, Mashxura; Mamatkulov, Orif (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Particular attention is paid to the design of the cotton separator used in the process of separating raw materials from air in the technology of primarily processing cotton. This process is crucial for preserving the natural quality indicators of cotton and cleaning it from small impurities. The cotton separator operates based on the efficiency of the mesh surface when separating air and raw material mixtures. The study investigated reforms aimed at increasing the useful surface area of the separator's mesh surface. This not only increases the efficiency of the separator, but also makes the process of cleaning cotton from small dust and impurities more efficient.